A model to optimize DNA sequences based on particle swarm optimization - Khalid, N. K.; Kurniawan, T. B.; Ibrahim, Z.; Yusof, Z. M. (2008)
In DNA based computation and DNA nanotechnology, the design of good DNA sequences has turned out to be an elementary problem and one of the most practical and important research topics. Although the design of DNA sequences is dependent on the protocol of biological experiments, it is highly required to establish a method for the systematic design of DNA sequences, which could be applied to various design constraints. Therefore, much work has focused on designing the DNA sequences to avoid incorrect or undesirable DNA computations. In this paper, a model for Particle Swarm Optimization (PSO) implementation is proposed to solve the DNA sequence design problem. PSO simulates a commonly observed social behavior where members of a group tend to follow the leader of the group. To demonstrate the correctness of the proposed model, a basic PSO with 10 particles is implemented to minimize an objective of DNA sequence design, which is the H-measure